Humor in Brooklyn Nine-Nine Sitcom Episodes: A Study of Cooperative Principles in Pragmatics - Mahadewi, Kadek Dinda Dwi; Laksminy, Luh Putu; Detriasmita Saientisna, Made (Humanis, 2023)
Humor is often used as a way to express emotions about specific topics. It is commonly delivered in the form of jokes and is frequently used in shows that portray the daily life of the characters, especially the ones that use verbal humor. This article aims to fill the gap in the study of the subject of the Cooperative Principle in Pragmatics, which is a complement to the issue analyzed. This study uses qualitative research to approach the data collected from a sitcom series, Brooklyn Nine-Nine. The study used the theory of the Cooperative Principle proposed by Paul Grice. The result of this study shows: (1) the TV series delivers humor by violating four of the Maxims, and (2) the violation of Maxims is required to help the contribution of the conversation in the TV series leads to be related to the audience.